2017
DOI: 10.1073/pnas.1708291114
|View full text |Cite
|
Sign up to set email alerts
|

Esco1 and Esco2 regulate distinct cohesin functions during cell cycle progression

Abstract: Sister chromatids are tethered together by the cohesin complex from the time they are made until their separation at anaphase. The ability of cohesin to tether sister chromatids together depends on acetylation of its Smc3 subunit by members of the Eco1 family of cohesin acetyltransferases. Vertebrates express two orthologs of Eco1, called Esco1 and Esco2, both of which are capable of modifying Smc3, but their relative contributions to sister chromatid cohesion are unknown. We therefore set out to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 41 publications
7
95
0
1
Order By: Relevance
“…3E). Because the cells lack functional ESCO1, all acetylation of SMC3 in these samples is ESCO2 dependent (Alomer et al, 2017). We found that in general the relative amount of SMC3 acetylation correlated with the amount of cohesion.…”
Section: The Esco2 N Terminus Contains Multiple Essential Motifsmentioning
confidence: 68%
See 4 more Smart Citations
“…3E). Because the cells lack functional ESCO1, all acetylation of SMC3 in these samples is ESCO2 dependent (Alomer et al, 2017). We found that in general the relative amount of SMC3 acetylation correlated with the amount of cohesion.…”
Section: The Esco2 N Terminus Contains Multiple Essential Motifsmentioning
confidence: 68%
“…The functional difference between ESCO2 and the related ESCO1 maps to their distinct N termini, as opposed to their conserved C terminal acetyltransferase domains (Alomer et al, 2017). This suggests that the N terminus of ESCO2 might be sufficient to promote localization to replication foci.…”
Section: Box C Ensures Association With Replication Focimentioning
confidence: 99%
See 3 more Smart Citations